Antimalarial drugs trigger lysosome-mediated cell death in chronic lymphocytic leukemia (CLL) cells. (July 2018) - Das, Subhadip; Dielschneider, Rebecca; Chanas-LaRue, Aaron; Johnston, James B.; Gibson, Spencer B.
Highlights: Anti-malarial drugs commercially available induce cell death in primary CLL cells These drugs kill CLL cells through lysosome disruption causing increased levels of ROS. Cathepsins released from the lysosomes participates in antimalarial drug-induced cell death. Stromal cells reduce cytotoxicity of antimalarial but fail to prevent their killing of CLL cells. Abstract: Lysosomes are the most acidic vesicles within mammalian cells and are promising targets for the treatment of breast cancer, glioblastomas and acute myeloid leukemia (AML). Our previous studies have shown that chronic lymphocytic leukemia (CLL) cells are also sensitive to lysosome disruption and cell death, by siramesine or chemotherapy. In the present study, we screened the antimalarial drugs, mefloquine, atovaquone, primaquine, and tafenoquine, for their effects on lysosome disruption and cytotoxicity in primary CLL cells. We found that mefloquine and tafenoquine could permeabilize lysosome membranes and induce cell death at doses that are clinically achievable. In contrast, these agents had less effect on normal B cells. Tafenoquine was most effective at inducing cell death, and this was associated with increased formation of reactive oxygen species (ROS) and lipid peroxidation. Addition of ROS scavengers blocked both tafenoquine- and mefloquine-induced cell death. Moreover, blocking the activity of cathepsins released from the lysosomes decreased tafenoquine-induced cell death. Taken together, lysosome disruption using antimalarial drugs is a novel approach for the treatment of CLL.